Inflation persistence: euro area and new EU Member States - Michal Franta; Branislav Saxa; Katerina Šmídková (European Central Bank (ECB), 2007)
Is inflation persistence in the new EU Member States (NMS) comparable to that in the euro area countries? We argue that persistence may not be as different between the two country groups as one might expect. We confirm that one should work carefully with the usual estimation methods when analyzing the NMS, given the scope of the convergence process they went through. We show that due to frequent breaks in inflation time series in the NMS, parametric statistical measures assuming a constant mean deliver substantially higher persistence estimates for the NMS than for the euro area countries. Employing time-varying mean leads to the reversal of this result and suggests similar or lower inflation persistence for the NMS compared to euro area countries. Structural measures show that backward-looking behavior may be more important component in explaining inflation dynamics in the NMS than in the euro area countries.
Keywords: E31; C22; C11; C32; 330; C11; C22; C32; Classification-JEL: E31; Keywords: Inflation persistence; New Hybrid Phillips curve; new Member States; time-varying mean; Inflationsbekämpfung; Preisrigidität; New-Keynesian Phillips Curve; EU-Staaten; EU-Mitgliedschaft